Analisis Pelaporan Unsafe Action dan Unsafe Condition dalam Upaya Pencegahan Kecelakaan Kerja di PT X: Analisis Pelaporan Unsafe Action dan Unsafe Condition dalam Upaya Pencegahan Kecelakaan Kerja di PT X - Prima Eka Wulandari (JURNAL MANAJEMEN MOTIVASI, 2026)
Reporting unsafe actions and unsafe conditions is a preventive measure for identifying hazards before they escalate into accidents. PT X, an oil and gas support services company, has implemented such reporting as part of its Occupational Safety and Health (OSH) program. This qualitative descriptive study analyzes the reporting implementation at PT X through in-depth interviews with the HSE Manager, Supervisor, and Staff, supported by field observation and document review. Results show that reporting has been carried out systematically through reporting, verification, hazard identification, follow-up, and periodic evaluation, supported by management commitment and worker participation, support workplace prevention. Keywords: Occupational Safety and Health (OSH); Unsafe Action; Unsafe Condition; Hazard Reporting; Workplace Accident Prevention